Pengembangan dan efektivitas model konseling behavioral teknik penguatan positif serta teknik modeling untuk meningkatkan kemandirian anak usia dini - Komang Sukma Pertiwi Dialektika; I Ketut Gading; Ni Ketut Suarni (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
This study aims to produce a design of a counseling guide, determine the validity of the contents of the guidebook, find out the practicality of the guidebook and know the effectiveness of the behavioral counseling guidebook with strengthening techniques and modeling techniques to increase early childhood independence. This study uses the research and development method using the 4D model (Define, Design, Develope, Dissiminate). The assessors were five experts in the field of guidance and counseling as well as PAUD teacher practitioners in schools. In this assessment using 28 questionnaires that refer to the validity of the contents of the guidebook, 30 questionnaire items that refer to the practicality of the guidebook and 10 items of child independence assessment found on the observation sheet. Then an analysis was carried out using the lawshe formula with the results of the content validity analysis getting the CVR for each item more than 0 (CVR> 0) and no items with less value were found; of 0 (CVR<0). The CVI score is 1, it can be interpreted that the feasibility of this guidebook is high for development, the practicality test of the guidebook on the assessment of 10 guidance and counseling practitioners is declared practical (90%), (4) the effectiveness of the guidebook obtains a sig (2-tailed) value 0.000 or below 0.05 so that it can be said that the behavioral counseling guidebook is effective for increasing children's independence and produces a behavioral guidebook with positive reinforcement techniques and modeling to increase early childhood independence.